AIRCRAFT WHICH NEARLY ENTERED THE WAR (1914-1915) - Jan Ploeger (Scientia Militaria, 2012)
Shortly after the outbreak of the First World War the Department of Defence was offered the services of a number of pilots and aircraft. A number of excerpts now follow.